Winter Street, ca. 1870-80 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view east of Winter Street, located between Washington Street to the east-southeast and Tremont Street to the west-northwest. Signage, street lights, and awnings adorn the facades of buildings lining both the north-northeast and south-southwest sides of the street. A street lamp is located in front of 19 Winter Street. A horse-drawn wagon is visible parked along the south-southwest side of Winter Street. 2 15/16 x 3 Stereographs